The anti-proliferative effects of type I IFN involve STAT6-mediated regulation of SP1 and BCL6. Issue 2 (1st June 2016) - Hsu, Yu-An; Huang, Chi-Chun; Kung, Yung-Jen; Lin, Hui-Ju; Chang, Ching-Yao; Lee, Kuan-Rong; Wan, Lei
Highlights: STAT6 contributed to the anti-proliferation effect of type I IFN. Interferon regulated Sp1 and BCL6 expression through STAT6 activation. STAT2 involved in interferon-mediated STAT6 activation. Abstract: Type I IFN-induced STAT6 has been shown to have anti-proliferative effects in Daudi and B cells. IFN-sensitive (DS) and IFN-resistant (DR) subclones of Daudi cells were used to study the role of STAT6 in the anti-proliferative activities. Type I IFN significantly increased STAT6 mRNA and protein expression in DS but not DR cells. STAT6 knockdown significantly reduced the sensitivity to IFN in both cell lines. The molecular targets and functional importance of IFN-activated STAT6 were performed by chromatin immunoprecipitation-on-chip (ChIP-on-chip) experiments in type I IFN-treated Daudi cells. Two target genes (Sp1 and BCL6) were selected from the ChIP-on-chip data. IFN-induced STAT6 activation led to Sp1 upregulation and BCL6 downregulation in DS cells, with only minimal effects in DR cells. siRNA inhibition of STAT6 expression resulted in decreased Sp1 and BCL6 mRNA and protein levels in both DS and DR cells. IFN treatment did not increase Sp1 and BCL6 expression in a STAT2-deficient RST2 cell line, and this effect was mitigated by plasmid overexpression of STAT2, indicating that STAT2 is important for STAT6 activation. These results suggest that STAT6 plays an important role in regulating Sp1 and BCL6 through STAT2 to exert the anti-proliferative effects of type I IFN.